Observer-based adaptive tracking control for a convection-reaction PDEs system with input constraints - Abdellaziz Binid (22963174) (2025)
This paper addresses two significant problems for a class exothermal plug flow tubular reactors, whose model is governed by nonlinear partial differential equations (PDEs), with temperature and reactant concentration as the state variables. The first problem tackled is the design of an exponential Luenberger-like observer specifically tailored for this class of systems. The second problem pertains to tracking pre-specified profiles of temperature and reactant concentration while considering input constraints. To overcome this, a Luenberger-like observer is used. The paper concludes by demonstrating that the chemical process states asymptotically approach balls with arbitrary radii, centered at the desired profiles. Numerical simulations are provided to showcase the effectiveness of the proposed approach. Other Information Published in: European Journal of Control License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ejcon.2025.101443